2010
DOI: 10.1021/jp110441e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Calcium Hydroxyapatite Nanoparticles Using Microreactor and Their Characteristics of Protein Adsorption

Abstract: The calcium hydroxyapatite Ca(10)(PO(4))(6)(OH)(2) (Hap) nanoparticles were prepared by using microreactor and employed these Hap nanoparticles to clarify the adsorption behavior of proteins. The size of Hap particles produced by the microreactor reduced in the order of a hardness of the reaction conditions for mixing Ca(OH)(2) and H(3)PO(4) aqueous solutions, such as flow rates of both solutions and temperature. Finally, the size of the smallest Hap nanoparticle became 2 × 15 nm(2), similar to that of BSA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 40 publications
1
52
0
1
Order By: Relevance
“…They reported that the particle size decreased sharply with increasing the continuous-phase flow rate, and a narrow size distribution was achieved at a high flow rate. Kandori et al [103] recently prepared smaller HAp nanoparticles (2 nm in width, 15 nm in length) by using a multichannel microreactor.…”
Section: Wet Chemical Precipitationmentioning
confidence: 99%
“…They reported that the particle size decreased sharply with increasing the continuous-phase flow rate, and a narrow size distribution was achieved at a high flow rate. Kandori et al [103] recently prepared smaller HAp nanoparticles (2 nm in width, 15 nm in length) by using a multichannel microreactor.…”
Section: Wet Chemical Precipitationmentioning
confidence: 99%
“…Accordingly, the maximum adsorption capacity of HA/CMC towards lysozyme was determined to be around 930-940 mg/g. Note that such lysozyme adsorption capacity is higher than that reported in literature [14,22]. This thus signifies the dual role of CMC, that is, as the template to regulate the biomimetic mineralization of HA with high affinity to proteins and itself as an effective adsorbent to immobilize the lysozyme.…”
Section: Adsorption Of Lysozyme Onto Ha/cmcmentioning
confidence: 56%
“…The solubility of HA increases with the decrease in the pH value of solution, that is, HA can be dissolved into nontoxic Ca 2+ and PO 4 3− ions in aqueous solution with a low pH value, e.g., in lysosome after cellular uptake or in acidic environment of solid tumors. The adsorption and release of proteins are strongly affected by the chemical and structural characteristics of HA [6,14], For instance, it has been shown that the needle-like HA exhibits a higher protein adsorption capacity than the spherical counterpart due to an increased adsorption sites on the surface [15]. Therefore, development of new HA with a high protein adsorption capacity remains attractive for protein drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…3) Tricalcium phosphate, Ca 3 (PO 4 ) 2 (TCP; Ca/P = 1.5) and Hydroxyapatite, Ca 10 (PO 4 ) 6 (OH) 2 (HAp; Ca/P = 1.67) are stable in the basic region. 4) HAp has been studied frequently among those phases, because it is excellently biocompatible and it is similar in structure and bio-chemical properties to inorganic materials involved in human bone and tooth as the primary inorganic component.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported that HAp was prepared with using a micro-reactor system. 10)12) The micro-reactor system may suppress such homogeneity or heterogeneity within a controllable limit of primary factors such as diffusion of solution, pH, reaction temperature and aging time after the reaction. The primary factors directly affect both the phase and the morphology of the yielded CPs crystallites.…”
Section: Introductionmentioning
confidence: 99%